Nonlinear model predictive control of a boiler unit: a fault tolerant control study - Korbicz, Józef (1951- ); Patan, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with a nonlinear model predictive control designed for a boiler unit. The predictive controller is realized by means of a recurrent neural network which acts as a one-step ahead predictor. Then, based on the neural predictor, the control law is derived solving an optimization problem. Fault tolerant properties of the proposed control system are also investigated.
Keywords: recurrent neural networks; process model; predictive control; fault detection; boiler unit